The association of cycle threshold value with clinical features in patients infected with Omicron variant - Wen Yang; Tao Tao; Jianping Zhang; Yuting Yao; Min Chen; Mingming Liu; Meiying Wu; Wei Lei (Virus Research)
This study investigated the correlation between epidemiological and clinical characteristics of patients infected with omicron variants and the cycle threshold (Ct value) for RT-PCR detection. The study population consisted of 115 patients with Omicron infection and the most common symptoms included fever (43.5 %), cough (38.3 %) and sore throat (29.6 %). Laboratory abnormalities were mainly lymphopenia, elevated globulins and elevated blood glucose. Univariate analysis found that older age (P < 0.001) and unvaccinated (P = 0.003) were associated with low Ct values (high viral load). Multivariate analysis showed that an elevated monocyte count (OR: 3.556; 95 % CI: 1.330–9.503) was associated with low Ct values, whereas being vaccinated (OR: 0.209; 95 % CI: 0.051–0.854) and lower serum sodium (OR: 0.137; 95 % CI: 0.051–0.367) were negatively associated with low Ct values. Studies have shown that factors such as monocyte count, vaccination status and serum sodium correlate with Ct values, suggesting the potential of Ct values as a clinical predictor, which could also provide a valuable reference for clinical decision-making.